VISITOR RESPONSE AS THE IMPACT OF SERVICE QUALITY IN PRIVATE HOSPITAL - Sayyida Sayyida; Alwiyah (STIE Mahardhika, 2023)
Lately, there have been a lot of complaints from patients and their families who go to the hospital because they are not satisfied with the services provided by the hospital. Hospitals are a service industry that is starting to become competitive because many private hospitals are competing. This study aims to determine the effect of the response of hospital visitors on the quality of hospital services. The research sample was the introduction of patients in three middle-class private hospitals in Surabaya, namely Adi Husada Hospital, Siloam Hospital and Premier Hospital. A total of 405 samples were divided into 2 groups, namely group 1 with 30 respondents and group 2 with 375 respondents. Data analysis of group 1 with Cronbach's Alpha aims to test the quality of the questionnaire before it is used to produce data analysis. To answer the research objectives, Structural Equation Model (SEM) analysis was carried out on the data in group 2. In this test, 5 data were detected as outliers so that the remaining 370 data were analyzed. The results show that the loyalty of patients and their families to visit the same hospital is influenced by the expectations and satisfaction of patients and their families and is influenced by the quality of hospital services they feel. Service quality has the greatest influence on patient and family loyalty.